The Comprehensive Literature Review of Surgical Management of Gastroschisis - Yosie Yulanda Putra; Ririn Azhari (International Medical Journal Corp. Ltd, 2024)
Background: The surgical management of gastroschisis has evolved significantly over the years, reflecting advancements in both surgical techniques and neonatal care. The literature indicates a marked increase in the birth prevalence of gastroschisis, with a notable reduction in mortality rates from 60% in the 1960s to 3-10% by the mid-1990s, although recent studies suggest that mortality rates have plateaued (J Bradnock et al., 2011). Literature Review: Innovative approaches, such as the use of composite mesh, have emerged to address cases where traditional fascial closure is not feasible, thus highlighting the adaptability of surgical methods to meet patient-specific needs (K. Dikshit et al., 2015). Moreover, the focus on low- and middle-income countries (LMICs) emphasizes the need for accessible and practical surgical strategies, particularly the application of preformed silos that can be managed by trained healthcare personnel in resource-limited settings (J Wright et al., 2018). Emerging research on fetal surgical interventions highlights the potential for proactive management strategies that could improve outcomes by addressing the defect before birth (Durmaz et al., 2022). This shift towards minimally invasive techniques reflects a broader trend in surgical management, emphasizing the importance of careful patient selection and timing of intervention. Finally, the implications of umbilical cord graft closure and its association with umbilical hernia development underscore the need for meticulous postoperative assessment and management, highlighting the complexities involved in the long-term care of these patients (Taher et al., 2022). Conclusion: In conclusion, the literature on the surgical management of gastroschisis reveals a dynamic and evolving landscape characterized by innovation and adaptability in surgical techniques. The advancements in surgical care, particularly the integration of minimally invasive approaches and the focus on practical solutions for resource-limited settings, are pivotal in enhancing patient outcomes. However, ongoing research is essential to address existing gaps in knowledge and to refine management strategies further.